Didaktika informatiky v príprave budúcich učiteľov informatiky a informačnej výchovy - Stoffová, Veronika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Cieľom štúdie je definovať didaktiku informatiky ako odborovú didaktiku a didaktiku programovania ako predmetovú didaktiku v príprave učiteľov informatiky.

The aim of the study is to define theme thodology of informatics as a union didactics and the methodology of programming as a subject didactics in informatics teacher training for elementary and secondary schools.
Didactics of computer science in informatics and information technologies education teacher training
Keywords: informatika; didaktika; didaktika informatiky; odborové didaktiky; predmetové didaktiky; informatics; computing; didactic of computer science; teaching of specific subject areas; subject didactics